ISOTOPIC ABUNDANCES OF MAGNESIUM - 24Mg, 25 Mg, 26 Mg IN THE ATMOSPHERES OF G-K - GIANTS - Kovtyukh, V. V.; Komarov, N. S.; Andrievsky, S. M.; Dulapchi, I. F. (Одеські астрономічні публікації, 2017)
The isotopic abundances of magnesium in the star of thin disk of Galaxy with various chromospheric activity were studied. We use the new data about molecular constants of radiation for isotopes 24Mg, 25Mg, and 26Mg. Values close to solar ratios are generally found.